Conversion of cattle manure into functional material to remove selenate from wastewater - Lee, Nahyeon; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik; Lee, Jechan (Chemosphere, 2021)
Herein, pyrolysis of cattle manure was conducted to synthesize an effective material for removing heavy metals (e.g., selenium) from water environments. To remove selenate from aqueous solution, iron-impregnated cattle manure biochar (Fe/CM–biochar) was synthesized. The Fe-impregnation was performed by pre-treating cattle manure before its pyrolysis. The pretreatment increased the biochar yield. Influence of various factors such as contacting time, initial selenate concentration, reaction temperature, pH, and presence of coexisting anions were explored by performing batch adsorption experiments. The selenate adsorption reached equilibrium within 15 min. The Langmuir model was better fitted to equilibrium adsorption data than the Freundlich model. The maximum adsorption capacity of Fe/CM–biochar was calculated to be 52.56 mg-Se/g, which is superior to other adsorbents reported in the literature. As the reaction temperature increased in the range (15–35) °C, selenate adsorption on Fe/CM–biochar showed an endothermic and nonspontaneous reaction. The enthalpy change during selenate adsorption was 18.44 kJ/mol, which ranges in physical adsorption. The increase of solution pH (3–11) reduced the selenate adsorption (46.4–37.7 mg-Se/g). The extent of co-existing anion impact on selenate adsorption followed an order of HPO42− > HCO3− > SO42− > NO3−. These results indicate that Fe/CM–biochar is an effective functional material for the removal of selenate from wastewater.
Keywords: Batch adsorption experiments; Bio chars; Cattle manures; Effective materials; Langmuir models; Pre-treatments; Reaction temperature; Se(ⅵ); Synthesised; Water environments; Adsorption; Animals; Cattle; Charcoal; Kinetics; Manure; Selenic Acid; Waste Water; Water Pollutants, Chemical; Biochar; Impregnation; Iron; Pyrolysis; Se(Ⅵ); Selenate